Enhanced magnetic properties through tailoring of morphology of electrospun strontium hexaferrite nanofibers - Nishtha Vats; Saket Sanjay Phadkule; Shrutidhara Sarma; Devendra Singh Negi; Badri Vishal; Sampat Raj Vadera; Durgamadhab Mishra (Scientific Reports)
Abstract This work reports a simple yet unique way of tailoring the morphology of M-type Strontium Hexaferrite, SrFe12O19 (SFO) particles inside the nanofibers. The reported materials were synthesized by the polymer-sol-assisted electrospinning technique followed by calcination. Calcination temperature and rate of heating play significant role in controlling the morphology of SFO nanofibers in terms of shapes, size and distribution thereby having a direct bearing on the resultant magnetic properties. The synthesized materials were investigated using X-ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), High Resolution Transmission Electron Microscopy (HRTEM), Thermogravimetric-Differential Thermal Analysis (TG-DTA), and Magnetic Property Measurement System (MPMS). The XRD analysis shows formation of almost phase pure SFO with very minute quantities of secondary phase as hematite. The FESEM images show wide range of morphologies of SFO nanofibers and specifically the nanoparticles present within the nanofibers (from irregular to platelet-like shape) thereby demonstrating the tailoring of morphologies of not only of nanofibers but nanoparticles within the nanofibers simply through variations of two parameters viz. calcination temperature and rate of heating. The TG-DTA results show that complete decomposition of PVP and formation of the SFO crystallization takes place at a much lower temperature of 422 oC. The room temperature hysteresis measurement showed that the sample calcined at 800 oC at heating rate of 10 oC/min has shown enhanced magnetic properties (Ms, Mr, and Hc) than the samples calcined at 600 oC and 950 oC. The HRTEM studies show that the variation in heating rate also yields interesting variations in morphology of nanoparticles and their arrangement within nanofibers. This research work has resulted in a unique pathway of synthesizing nanofibers with controlled and variable morphology.